Pengaruh Promosi, Potongan Harga dan Gratis Ongkir terhadap Perilaku Konsumtif mahasiswa pada Marketplace Shopee - Howandi, Rani Desiana; Cendana, Sylvia; Panggabean, Maya Sabirina; Nurmasari Pane, Dewi (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze the effect of promotions, discounts, and free shipping on the consumer behavior of students of the Faculty of Economics, Universitas Prima Indonesia. The study was conducted in Medan, North Sumatra, from February to April 2024 using a quantitative method with a causal approach. The sampling technique used the Lemeshow method with accidental sampling, producing a sample based on a maximum estimate of 50% and an error rate of 10%. Primary data were collected through a survey using a questionnaire and analyzed using validity, reliability, and multiple linear regression tests. The results of the classical assumption test showed that the data were normally distributed, there was no multicollinearity, and met the homoscedasticity assumption. Descriptive statistical analysis describes that the variables of promotions, discounts, free shipping, and consumer behavior have average values ​​that are relevant to the research hypothesis. The results of multiple linear regression indicate that promotions, discounts, and free shipping have a significant effect on consumer behavior partially and simultaneously, as shown by the t-test and F-test with a significance level of 5%. The coefficient of determination (Adjusted R²) shows that the independent variables are able to explain variations in consumer behavior adequately. Keywords: Free Shipping, Consumer Behavior, Promotion, Discounts, Shopee